2021
DOI: 10.1007/s40201-021-00674-1
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation processes for chlorpyrifos removal from aqueous solution: a systematic review

Abstract: Chlorpyrifos (CPF), an organophosphate insecticide, due to its high efficiency and low cost is widely used in the agricultural industry. CPF may lead to lung deficiency, central nervous system damage, developmental and autoimmune disorders. In recent decades, the advanced oxidation processes (AOPs) have been considered in water and wastewater treatment due to their high efficiency in decomposition of organic and inorganic compounds, specially hardly biodegradable or non-biodegradable compounds. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…Few reviews have reported some examples over the destruction of insecticides by sulfate radical‐based AOPs. In our previous review [14], the treatment of insecticide solutions by means of Fenton‐based processes was detailed exposing some comparative studies with activated PS. Matafonova and Batoev [25] and Zawadzki [26] described the general behavior of the removal of pollutants by UV and visible light treatments, respectively, whereas the overview of Vagi and Petsas [2] considered the remediation of waters with organochlorine and organophosphorus pesticides by AOPs up to 2018 (see Table 1).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Few reviews have reported some examples over the destruction of insecticides by sulfate radical‐based AOPs. In our previous review [14], the treatment of insecticide solutions by means of Fenton‐based processes was detailed exposing some comparative studies with activated PS. Matafonova and Batoev [25] and Zawadzki [26] described the general behavior of the removal of pollutants by UV and visible light treatments, respectively, whereas the overview of Vagi and Petsas [2] considered the remediation of waters with organochlorine and organophosphorus pesticides by AOPs up to 2018 (see Table 1).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…•− ) generated by persulfate have longer half-lives, higher redox potentials, and better selectivity compared to hydroxyl radicals (•OH) [23,24]. Shah et al prepared Fe-ZnO using the sol-gel method and used it in activating the persulfate process; results demonstrated that the generation of high concentrations of SO 4…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, persulfate-based advanced oxidation processes (AOPs) have gained increasing attention. This is because sulfate radicals (SO 4 •− ) generated by persulfate have longer half-lives, higher redox potentials, and better selectivity compared to hydroxyl radicals (·OH) [ 23 , 24 ]. Shah et al prepared Fe-ZnO using the sol-gel method and used it in activating the persulfate process; results demonstrated that the generation of high concentrations of SO 4 •− and ·OH have strong oxidation effect on CPY degradation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…OP compounds are among the most widely used insecticides worldwide [ 4 , 5 ]. OPs such as parathion and malathion can undergo biotransformation via cytochrome P450 enzymes to acquire more toxic forms [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%